Comparative light and scanning electron microscopy in authentication of adulterated traded medicinal plants. Issue 7 (17th April 2019) - Ahmed, Sidra N.; Ahmad, Mushtaq; Zafar, Muhammad; Rashid, Sofia; Yaseen, Ghulam; Sultana, Shazia; Siddiq, Zafar; Kilic, Omer; Ozdemir, Fethi A.; Kayani, Sadaf
Abstract: The medicinal plants are utilized globally considering the cheap and chemical free source, but their correct identification and authentication is prerequisite for safety and efficacy of plant‐based medicines. The present study encompassed traded medicinal plants (16) with high therapeutic value from diverse families like Brassicaceae, Berberidaceae, Malvaceae, Salicaceae, Myrtaceae, Papilionaceae, Ascelpiadaceae, Colchicaceae, Violaceae, and Vitaceae for detailed microscopic study of characters that is, morphology, pollen shape and sizes, P/E ratio, pore length and width, spine length, colpi dimensions, and exine sculpture pattern. The plants showed noteworthy differences in microscopy of Wattakaka volubilis having pollinia, translator and corpusculum like structures while pores were visible in Colchicum luteum, Alcea rosea, and Hibiscus syriacus . The spines were observed in Centipeda minima, A. rosea, and H. syriacus being dimorphic spines in A. rosea and monomorphic in H. syriacus . The exine sculpturing pattern was reticulate in mostly studied plants however distinctive exine pattern was noted in Berberis aristata and Berberis lyceum . The highest polar diameter, equatorial diameter and exine thickness among studied plants were observed in H. syriacus (161 μm), C. luteum (50 μm) and Vitis jacquemontii (1.10), respectively. Thus, microscopy of medicinal plants in addition to other taxonomic evidence offers a supportive skill in authentication, consequently utilization by local consumers and pharmaceutical industries. Abstract : Comparative LM and SEM are useful palynological techniques to authenticate genuine source of traded medicinal plants. Detailed microscopy participates significant role in the identification of original plant species from their adulterants.